Pengaruh Modal, Lama Usaha dan Lokasi Terhadap Pendapatan Pedagang Pasar Pasca Relokasi - Khasan Setiaji; Ana Listia Fatuniah (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2018)
This study aims to find out the effect of capital, length of trading, and location toward the traders income Johar market in Semarang City both simultenously and partially. The sample is 92 traders. The result of the study showed that the significant value of 0,000 < 0,05 and the value of Fcount (74,922) is higher than Ftable(2,71) and Adjust R Square of 0,709 (70,9%). Capital gives positive effect on traders income in Johar market Semarang obtains the significant value of 0,000 < 0,05 and the value of tcount(5,853) higher than ttable (1,987) and r-squareof 27,9%. The length of trading gives positive effect on traders income in Johar market Semarang obtains the significant value of 0,000< 0,05 and the value of tcount(3,635) higher than ttable(1,987) and r-squareof 13,0%. Location gives positive effect on the traders income in Johar market Semarang obtains the significant value of 0,000 < 0,05 and the value of tcount(4,658) higher than ttable (1,987) and r-square of 19,8%. The conclusion is that there is a positive effect of capital, length, and location of trading toward the traders income Johar market in Semarang City.